Integration of pretreatment tumor markers in a nomogram model for prognostic prediction of FIGO stage I endometrial cancer: A multi‐institutional cohort study - Lin, Hao; Wu, Chen‐Hsuan; Ou, Yu‐Che; Huang, Szu‐Wei; Fu, Hung‐Chun (International journal of gynecology and obstetrics, 2024)
Objective Traditionally, the prognosis of patients with FIGO stage I endometrial cancer is determined by clinicopathological risk factors. In this study, we assessed the potential contribution of pretreatment carcinoembryonic antigen (CEA) and carbohydrate antigen‐125 (CA‐125) levels to estimating the prognosis of these patients and aimed to develop and validate a prognostic nomogram. Methods This retrospective study included patients with FIGO stage I endometrial cancer who underwent treatment between January 2009 and December 2021 in the four institutes of Chang Gung Memorial Hospital. To identify optimal cutoff values of CEA and CA‐125 for predicting survival, receiver operating characteristic (ROC) curves were generated, the Kaplan–Meier method was used to estimate survival, and a Cox regression model was used to analyze the independent prognostic factors. Finally, a nomogram and calibration curve were constructed to predict patient survival probability. Results Of the 1559 patients evaluated, the optimal cutoff values of CEA and CA‐125 were 1.44 ng/mL (area under the ROC curve [AUC] 0.601) and 39.77 U/mL (AUC 0.503), respectively. Multivariate Cox regression analysis showed that pretreatment CEA (hazard ratio [HR] 2.11, 95% confidence interval [95% CI] 1.35–3.28), CA‐125 (HR 2.07, 95% CI 1.31–3.27), age >70 years (HR 12.54, 95% CI 5.05–31.11), myometrial invasion >50% (HR 1.69, 95% CI 1.03–2.73), non‐endometrioid histology (HR 1.83, 95% CI 1.14–2.95), high‐grade tumor (HR 2.41, 95% CI 1.46–3.97), and lymphovascular space invasion (HR 2.32, 95% CI 1.26–4.25) were significant variables associated with overall survival. These factors were used to construct the nomogram model, which showed good concordance and accuracy. Conclusions Integration of pretreatment CEA and CA‐125 in a prognostic nomogram is feasible. Our prediction model has the potential to assist clinicians in guiding appropriate clinical practice. Synopsis Pretreatment CEA and CA‐125 levels should be incorporated into the prognostic evaluation for early‐stage endometrial cancer.